PENGARUH PENERAPAN MODEL DISCOVERY LEARNING DISERTAI STRATEGI PEMBELAJARAN AKTIF TIPE TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA KELAS VII - Tri Wulan Puteri Angraini; Rahmi Rahmi; Hafizah Delyana (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
Background of The research by learning outcome student which still many below Complete Criterion Minimize (CCM). Other than that study process only predominated by group owning high ability. Purpose of this research are to know do there are influence model discovery learning accompanied active learning strategy of teka-teki silang type to learning outcome student of VII class SMP Negeri 9 Batanghari. Design of this research is pre-eksperimen research with research design of pre-test and post-test group.  The population in research was all student of  VII class SMP Negeri 9 Batanghari. Technique intake of sampel use Purposive Sampling, selected as class of sampel is VII B class. The research Instrument is pre-test and post-test form essay. Technique analyse of pre-test and post-test the used t test one side. Result of this result was learning outcome student after using model discovery learning accompanied active learning strategy of teka-teki silang type better of mean learning outcome of student before using model discovery learning accompanied active learning strategy of teka-teki silang type.